Pendekatan Metode Six Sigma (DMAIC) untuk Peningkatan Kualitas Produk Boncabe di CV Kobe & Lina Food - Dede Rukmayadi; Sri Sugiarti (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
CV . Kobe & Lina Food is engaged in manufacturing food industry. Data processing is done to achieve continuous quality improvement towards the target of Six Sigma, which is using the methodology DMAIC ( Define Measure Analyze Improve Control ). Characteristics of product weight have 84,100 DPMO to the sigma level of 2.88, and disability packaging process has 6,010 DPMO to the sigma level of 4.01. Known to cause defects largest packaging process due to setting the machine with a percentage of 27% of the total disability. The cause of the weight that is not standards-compliant due to the negligence of the operator. Fixes a problem with the method 5W - 2H. This method is carried out improvements to the working methods of inspectors and operators. Implementation and measurement re- sigma level, for the weight of bonCabe sigma level to 4.30. To improve the quality of the products the company needs to implement a Six Sigma program.Keywords: Quality, Six Sigma, DMAIC, Defect.